Performance improvement for reduction of resonance in a grid-connected inverter system using an improved DPWM method - Park, Jin Hyuk; Lee, Kyo Beum (Energies, 2018)
This paper proposes discontinuous pulse width modulation (DPWM) for a grid-connected inverter system using an LCL-filter which consists of two inductors and a capacitor that is connected in parallel per phase. The modulation signal is discontinuously changed, and the harmonic voltages are generated in the wide frequency range at the output terminal of the inverter when the conventional DPWM is used. If these harmonic voltages are present in the resonance frequency band by an LCL-filter, then the resonance problem of the grid current occurs. To suppress the resonance problem, the proposed DPWM injects the sixth harmonic to the modulation signal. Therefore, in the improved DPWM, harmonic voltages at the output terminal of the inverter are sufficiently reduced because the discontinuous change of the modulation signal disappears. The proposed DPWM method is verified by a Powersim (PSIM) simulation (Powersim Inc., Rockville, MD, USA) and experiments with a 3-kW neutral-point clamped (NPC)-type grid-connected inverter system.
Keywords: Discontinuous pulse width modulations (DPWM); Discontinuous PWM; Grid connected inverters; LCL filters; Neutral point clamped; Performance improvements; Resonance current; Resonance frequencies; Discontinuous PWM; LCL-filter; NPC-type grid connected inverter; Resonance current